2014
DOI: 10.1590/s1677-5538.ibju.2014.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel non-biological bench model for the training of percutaneous renal access

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: The percutaneous renal access (PRA) is the most critical step of percutaneous renal surgery (PRS). For the training of PRA in the lab, a novel non-biological bench model was developed and set for validation test. Materials and Methods: Experts in PRS (> 60 cases) and novices were included to perform fluoroscopy guided PRA on the model. Overall time, X-ray exposure time and puncture attempts were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Questionnaire 1 for doctors was designed according to the literature to evaluate the 3D-printed prototype [ 5 , 6 ]. The questionnaire included five aspects: (1) overall satisfaction with the 3D prototype; (2) degree of verisimilitude of the 3D prototype to the actual fracture; (3) detailed demonstration of the anatomical structure of the ankle joint by the 3D prototype; (4) detailed demonstration of the fracture-fragment-displacement direction and fracture-injury degree by the 3D prototype; and (5) usefulness of the 3D prototype as a preoperative planning tool.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaire 1 for doctors was designed according to the literature to evaluate the 3D-printed prototype [ 5 , 6 ]. The questionnaire included five aspects: (1) overall satisfaction with the 3D prototype; (2) degree of verisimilitude of the 3D prototype to the actual fracture; (3) detailed demonstration of the anatomical structure of the ankle joint by the 3D prototype; (4) detailed demonstration of the fracture-fragment-displacement direction and fracture-injury degree by the 3D prototype; and (5) usefulness of the 3D prototype as a preoperative planning tool.…”
Section: Methodsmentioning
confidence: 99%
“…22 Other nonbiological bench models used prototyping or 3D printing. [23][24][25][26] Only one study reported the use of anesthetized live pigs as module 1 of the Modular Training Scheme, which included renal puncture, tract dilatation using the Amplatz dilators, and orientation with the nephroscope in a live pig. 27 The PERC MentorÔ (Simbionix, Cleveland, OH) was the only VR simulator that has been validated for training and assessment of PCA skills.…”
Section: Resultsmentioning
confidence: 99%
“…1 Various simulators are available to aid PCNL apprenticeship. These range from phantom kidney models 11 to sophisticated virtual reality trainers such as the PERC Mentor. 12 These are useful adjuncts to clinical apprenticeship.…”
Section: Discussionmentioning
confidence: 99%